CONVERSION OF INULIN INTO CARBOXYMETHYL DERIVATIVES BY THE SUSPENSION METHOD IN ISOPROPYL ALCOHOL MEDIUM. (Multidisciplinary Journal of Science and Technology, 2025)
This study investigates the synthesis of carboxymethylinulin via  the suspension method in an isopropyl alcohol medium. The effects of  mercerization, temperature, reaction time, and the concentration of the alkylating  reagent on the physicochemical properties of the reaction products are examined.  The results demonstrate that the degree of substitution of inulin esters, as well as  their molecular characteristics, are strongly dependent on reaction conditions.  These findings highlight the potential of carboxymethylated inulin as a functional  derivative with valuable properties for use in food, pharmaceutical, and chemical  industries. These findings could serve as a basis for further research on the  industrial applications of carboxymethylated inulin.